FACTORS PREDISPOSING TO INCREASED PREVALENCE OF ANTEPARTUM HAEMORRHAGE AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE AT KISENYI HEALTH CENTRE IV, KAMPALA DISTRICT. A CROSS-SECTIONAL STUDY. - ARNOLD AKONJA; Vincent Kalungi (Student's Journal of Health Research, 2023)
Background: The purpose of the study was to assess the factors predisposing to the increased prevalence of antepartum hemorrhage among pregnant women attending antenatal care at Kisenyi Health Centre IV, Kampala district. The specific objectives were to find out the individual factors, community-related factors, and Health facility-related factors predisposing to increased prevalence of antepartum hemorrhage. Methodology: A cross-sectional study design with simple random sampling as the sampling technique. Data was collected on a sample size of 50 respondents using a semi-structured questionnaire written in the English language with open and closed-ended questions as the data collection tool, analysis was done manually by sheets, pens, and paper entered in an Excel computer program presented in tables and figures and then interpreted. Results:  With regards to the individual factors, (60%) of the respondents had ever experienced anemia during pregnancy and the majority (60%) had ever used alcohol or smoked tobacco during pregnancy. Regarding the community-related factors, the majority (88%) of the respondents reported that Kisenyi HC IV was the nearest health center for ANC to them, the majority (74%) had ever been delivered by traditional birth attendants and finally, the majority (64%) had ever used local herbs during pregnancy. Regarding the Health facility-related factors, almost all (98%) of the respondents reported that the Facility was inadequately staffed, and the majority (72%) reported that the health facility was inadequately equipped to effectively manage pregnancy-related conditions like Antepartum hemorrhage. Conclusion.  Despite the commendable measures put in place to manage Antepartum hemorrhage and related conditions, a lot still needs to be done especially with health facility practices and individual measures with regards to the topic.  Recommendation.  The Ministry of Health and the health facility should recruit more staff and procure more equipment for use, especially for the Maternity unit at the Health Centre.